Analysis of the Use of Tubular Scaffoldings at PT. Medco E&P Malaka Asset Block-A Aceh Timur - Fadly; Yuslinda; Iqbal (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
Tubular scaffolding is a construction system that uses steel pipes as a basic frame to support various construction materials, such as sand, stone, cement, and wood. The aim of the study is the types/components that make up tubular scaffolding, the use of tubular scaffolding in accordance with applicable regulations, and how to install, maintain, and dismantle tubular scaffolding used at PT. Medco E&P Malaka. In this study, the conditional probability analysis method was used to determine the use of tubular scaffolding used by PT. Medco E&P Malaka regarding the types/components and applicable regulations. The results of conditional probability data analysis from this research show that the types/components that make up tubular scaffolding and also the regulations for the use of tubular scaffolding used at PT. Medco E&P Malaka show a P(H | E comb) value of 1.00. From the results of this analysis, it can be interpreted that the use of tubular scaffolding meets the types/components and regulations applicable to the erection of a scaffold.